OPTIMIZATION OF BASALT FIBER CONCRETE COMPOSITION - Rakhimov Rasuljon Ravshanbek o‘g‘li (Journals Park Publishing, 2024)
This article studies the composition of basalt fiber concrete. It is aimed at determining the optimal composition for fiber concrete in an experimental setting. The article provides information about the optimal composition of basalt fiber for fiber concrete.
Keywords: Basalt, fiber, fiber concrete, fiberconcrete, construction.